Analysis of remote learning (ARDE) in basic education students in Colombia - Murcia Rodríguez, Jennifer; González González, Jhoana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The students of the educational institutions of basic and secondary education in Colombia and in the world, had to face new realities and situations of their academic process, due to the 2020 health crisis due to the COVID 19 virus, which has prevented around of 1,370 million students do not attend school under traditional education conditions, in Latin America more than 156 million children and young people, according to UNESCO, and in Colombia more than 9.4 million children in initial, basic and secondary education according to figures of the MEN Colombia.